2000
DOI: 10.1086/308411
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray–emitting Atmospheres of B2 Radio Galaxies

Abstract: We report ROSAT PSPC spatial and spectral analyses of the eight B2 radio galaxies NGC 315, NGC 326, 4C 35.03, B2 0326]39, NGC 2484, B2 1040]31, B2 1855]37, and 3C 449, expected to be representative of the class of low-power radio galaxies. Multiple X-ray components are present in each, and the gas components have a wide range of linear sizes and follow an extrapolation of the cluster X-ray luminosity/temperature correlation, implying that there is no relationship between the presence of a radio galaxy and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
84
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 23 publications
(60 reference statements)
23
84
0
Order By: Relevance
“…Miller et al 1999;Worrall & Birkinshaw 2000). Thus radio galaxies appear to be markers of similar external environments.…”
Section: Owen Ledlow And: Eilekmentioning
confidence: 98%
“…Miller et al 1999;Worrall & Birkinshaw 2000). Thus radio galaxies appear to be markers of similar external environments.…”
Section: Owen Ledlow And: Eilekmentioning
confidence: 98%
“…14). Worrall & Birkinshaw (2000) reported, for the cluster surrounding NGC 326, a core radius of ∼171 h −1 kpc and a pressure ranging from 7 × 10 −12 h 1/2 dyne cm −3 to 5 × 10 −12 h 1/2 dyne cm −3 at 100 kpc from the source. Therefore the inner radio lobes appear to be close to the pressure of the external gas while the wings appear to be under-pressured by a factor of 10.…”
Section: Lobes and Wingsmentioning
confidence: 99%
“…The first detailed studies of the intergalactic medium surrounding NGC 326 were done by Worrall et al (1995) and Worrall & Birkinshaw (2000). The region containing the source was imaged in soft X-ray with the ROSAT PSPC.…”
Section: Introductionmentioning
confidence: 99%
“…A direct measurement from X-ray data is used if available. Otherwise, we assume kT = 1 keV [based on our observations of the environments of low-redshift FRI objects; Worrall & Birkinshaw (1994, 2000a] for sources which inhabit low-luminosity X-ray environments, and a temperature derived from the temperature-luminosity relation (as discussed in paper I) for the high-luminosity objects. Where we estimate the temperature, we assume that the X-ray emission can be described with a Raymond-Smith model with 0.5 cosmic abundance.…”
Section: Sources With Modelled Atmospheresmentioning
confidence: 99%
“…For example, Arnaud et al (1984) found that the archetypal classical double 3C 405 (Cygnus A) had a minimum lobe pressure slightly higher than the external pressure, and Miller et al (1985) argued that upper limits on the X-ray emission from a small sample of lower-power FRII sources implied that they were unconfined by an external atmosphere. However, lower-power FRI sources inhabit a range of environments, from poor groups to rich clusters, and it is now well established that the minimum pressures in their kpc-scale radio structures are almost always lower, by an order of magnitude or more, than those in the X-ray-emitting gas (Morganti et al 1988; c 0000 RAS Killeen, Bicknell & Ekers 1988;Feretti et al 1990;Taylor et al 1990;Feretti, Perola & Fanti 1992;Böhringer et al 1993;Worrall, Birkinshaw & Cameron 1995;Hardcastle, Birkinshaw & Worrall 1998b;Worrall & Birkinshaw 2000a). Subsequent observations with ROSAT have suggested that the minimum pressures in some FRIIs are also in fact lower than those in the X-ray emitting gas Leahy & Gizani 1999).…”
Section: Introductionmentioning
confidence: 99%